KAJIAN KANDUNGAN ZAT GIZI DAN SIFAT SENSORIS LEDOK DARI BEBERAPA JENIS UMBI-UMBIAN - I Wayan Suarta; Ni Made Yusa; I Ketut Suter (Department of Food Science and Technology Study Program, Faculty of Agricultural Technology, Udayana University, 2013)
The aim of the study was to determine the nutrition content and sensory properties of ledokwhich made from various types of tubers. Experiments designed randomized block design whichcontains of six tubers treatment: yellow sweet cassava, yellow sweet potato varieties papua selulosa,purple sweet potato varieties RIS 03065-03, orange sweet potato varieties sari, white sweet potatovarieties sukuh, and white sweet potato varieties cengkuang. Each treatment was repeated three timesacquired 18 units of the experiment. The observation of parameters in this study were the moisturecontent, ash content, fat content, protein content, carbohydrate content, antioxidant capasity, sensoryproperties including color, aroma, taste, texture and overall acceptance. The data obtained wereanalyzed by analysis of variance, and if there are significant differences between treatments followedby Duncan Multi Range Test (DMRT).The results showed that, the use of types of tubers have significant effect on the content of fat,protein, carbohydrate, antioxidant capasity and sensory properties of the color, flavor, and texture, andwas not significant on the moisture content, ash content and sensory properties of the flavor andoverall acceptance. The best ledok was produced from purple sweet potato varieties RIS 03065-03with the following characteristics: moisture content 73,91% , ash content 0,69%, 3,14% fat content,protein content 10,58%, carbohydrate content 11,67%, antioxidant capasity 91,26% and overallacceptance (rather like)